2020
DOI: 10.3390/ma13184044
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Structural and Electrical Properties of BaLnCo2O6 Positrodes

Abstract: The application of double perovskite cobaltites BaLnCo2O6−δ (Ln = lanthanide element) in electrochemical devices for energy conversion requires control of their properties at operating conditions. This work presents a study of a series of BaLnCo2O6−δ (Ln = La, Pr, Nd) with a focus on the evolution of structural and electrical properties with temperature. Symmetry, oxygen non-stoichiometry, and cobalt valence state have been examined by means of Synchrotron Radiation Powder X-ray Diffraction (SR-PXD), thermogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…148 and 149, but from the temperature dependences of unit cell parameters by subtracting the low-temperature linear trend from the total ε values assuming temperature-independent TEC. In this respect, the volumetric chemical expansion of NdBaCo 2 O 6– δ determined in a similar manner by Cherepanov et al 248 from the dilatometric experiments coincides with that measured by Szpunar et al , 234 but is visibly greater than that found by Cox-Galhotra et al 148 (see Fig. S4 in the ESI†).…”
Section: Some Peculiarities and Trends In The Chemical Expansion Of O...supporting
confidence: 87%
See 2 more Smart Citations
“…148 and 149, but from the temperature dependences of unit cell parameters by subtracting the low-temperature linear trend from the total ε values assuming temperature-independent TEC. In this respect, the volumetric chemical expansion of NdBaCo 2 O 6– δ determined in a similar manner by Cherepanov et al 248 from the dilatometric experiments coincides with that measured by Szpunar et al , 234 but is visibly greater than that found by Cox-Galhotra et al 148 (see Fig. S4 in the ESI†).…”
Section: Some Peculiarities and Trends In The Chemical Expansion Of O...supporting
confidence: 87%
“…8, where the measurement results at similar temperatures are presented for RBaCo 2 O 6– δ (R = Pr, Nd, Gd), β a ≈ − β c for these double perovskite cobaltites, and their chemical expansion is close, taking into account the scatter in the data. 123,148,149 However, when all available experimental data for each of these oxides are considered, 31,123,144,148,149,233–235 it is immediately seen (Fig. S1–S3 in the ESI†) that the ε chem ( δ ) values do not often coincide well except for GdBaCo 2 O 6– δ , for which the results of Mogni et al , 233 Tsvetkov et al 123 and Chatterjee et al 31 agree with each other in the overlapping δ ranges.…”
Section: Some Peculiarities and Trends In The Chemical Expansion Of O...mentioning
confidence: 87%
See 1 more Smart Citation
“…The positrode performance is what limits current electrochemical devices based on PCCs and much effort was put into their development [ 10 , 11 , 12 , 13 ]. Recently, we have focused on the group of BaLnCo 2 O 6 (Ln—a lanthanide) perovskite compounds that showed promising properties for application as positrodes [ 14 , 15 , 16 ]. This system exhibits high electrical conductivity in a wide temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…Another set of papers deals with the development of new or application-specific approaches, namely laser interferometry techniques for high precision measurements on non-standard samples, such as composite truss structures [ 5 ]; measurements of high temperature compressive creep in spark plasma sintering apparatuses [ 6 ]; measurements of the density of liquid oxides with aero-acoustic levitators [ 7 ]; and the simultaneous estimation of thermal conductivity and heat capacity in metal alloys [ 8 ].The range of materials covered includes polymers [ 9 , 10 ]; natural complex inorganic materials, such as natural sorbents [ 1 ] and industrial-grade thermal insulation [ 4 ]; single phase ceramic materials, such as spinel MgAl 2 O 4 [ 11 ], rare earth sesquioxides [ 12 ], and double perovskite cobaltites [ 13 ]; metals, alloys, and intermetallic compounds [ 8 , 14 , 15 , 16 ].…”
mentioning
confidence: 99%